Accuracy of the Bronchoalveolar Lavage Enzyme-Linked Immunospot Assay for the Diagnosis of Pulmonary Tuberculosis: A Meta-analysis. Issue 12 (March 2016) - Pang, Caishuang; Wu, Yanqiu; Wan, Chun; Shen, Konglong; Hu, Yuzhu; Yang, Ting; Shen, Yongchun; Wen, Fuqiang
Abstract : Abstract: Assessing of local immune response may improve the accuracy of pulmonary tuberculosis (PTB) diagnosis. Many studies have investigated diagnosing PTB based on enzyme-linked immunospot (ELISPOT) assay of bronchoalveolar lavage (BAL) fluid, but the results have been inconclusive. We meta-analyzed the available evidences on overall diagnostic performance of ELISPOT assay of BAL fluid for diagnosing PTB. A systematic literature search was performed using PubMed, Embase, Wangfang, Weipu, and CNKI. Data were pooled on sensitivity, specificity, positive likelihood ratio (PLR), negative likelihood ratio (NLR), and diagnostic odds ratio (DOR). Overall test performance was summarized using summary receiver operating characteristic curves and the area under the curve (AUC). Deeks test was used to test for potential publication bias. Seven publications with 814 subjects met our inclusion criteria and were included in this meta-analysis. The following pooled estimates for diagnostic parameters were obtained: sensitivity, 0.90 (95% CI: 0.85–0.94); specificity, 0.80 (95% CI: 0.77–0.84); PLR, 5.08 (95% CI: 2.70–9.57); NLR, 0.13 (95% CI: 0.06–0.28); DOR, 49.12 (95% CI: 12.97–186.00); and AUC, 0.96. No publication bias was identified. The available evidence suggests that ELISPOT assay of BAL fluid is a useful rapid diagnostic test for PTB. The results of this assay should be interpreted in parallel with clinical findings and the results of conventional tests.